Evaluating AES and RSA Performance in MANETs for Mobile Agent Based Communication - Kaur, Mandeep (Thapar University, 2017)
Mobile ad hoc networks (MANETs) are a type of wireless ad hoc network (WANETs). MANETs consists of peer-to-peer, self-forming and self-healing network. It is a collection of mobile devices which can form a temporary network if there is no fixed infrastructure provided. The mobile hosts don’t need assistance of base stations for communication with each-other. They can be initiated at any moment of time and organized quickly everywhere because there is no difficulty in setting up the infrastructure. Due to lack of centralized architecture, security becomes the crucial aspect of ad-hoc network. The mobility of nodes also makes the network more prone to attacks. Security is a recent active topic for research in wired networks; even then, MANET has some nontrivial challenges that need a secure design. In order to deal with this issue, we have worked on mobile agent model. Mobile agents are software modules that contain data and code with themselves. They are able to move autonomously from one host to other to perform tasks and automatically come back to the host where they were initialized. Although they have so many qualities such as dynamism, autonomy, flexibility etc. that are required for some disciplines yet Mobile Agent have some limitations mainly the security issues due to mobility. In our work, we have secured mobile agents’ communication using AES and RSA algorithms in a MANET environment. The time taken to perform encryption and decryption by agents has shown the effective results using the proposed communication model.
Keywords: Manet, Mobile Agent, Security